No Difference Between Trabecular Metal Cones and Femoral Head Allografts in Revision TKA: Minimum 5‐year Followup. Issue 1 (January 2017) - Sandiford, Nemandra A.; Misur, Peter; Garbuz, Donald S.; Greidanus, Nelson V.; Masri, Bassam A.
Abstract: Background: Encouraging clinical results have been reported with the use of femoral head structural allografts and, more recently, trabecular metal cones for the management of large structural defects of the femur and tibia during revision total knee arthroplasty (TKA). However, to our knowledge, there are no published studies comparing these two techniques. Questions/purposes: Compared with bulk allografts, do trabecular metal cones result in (1) better validated outcomes scores; (2) a lower risk of loosening or revision at 5 years; and (3) fewer surgical complications when used for the management of bone loss in revision TKA? Methods: Between 2002 and 2008, three surgeons performed 450 TKA revisions, 45 (10%) of which were performed using augmentation of host bone; in those, femoral head allograft was used in 30 (75%) and trabecular metal cones in 15 (25%). From 2002 to 2007, femoral head allografts were used in all patients (28 patients); from 2007 to 2008, trabecular metal augments were used in all patients. There was a period of 1 year (16 knees) in which there was some overlap; during that time, femoral head structural allografts were used in cases in which we were unable to fit the defect or achieve adequate stability with trabecular metal cones. Followup was at a mean of 9 years (range, 5‐12 years). No patients were lost to followup. Knee function and quality of life were assessed using the Oxford Knee Score, WOMAC, SF‐12, and the UCLA activity score. Radiographs were assessed for signs of loosening. Surgical complications included superficial or deep infections, iatrogenic fractures, symptomatic deep venous thromboses or pulmonary emboli, and blood loss requiring transfusion; these were obtained from our database and from review of patients' charts. Results: The mean Oxford Knee Score in the allograft and trabecular metal cone groups was 91 (SD 10) and 91 (SD 14), respectively (95% confidence interval [CI], 88‐94; p = 0.29). Mean WOMAC scores were 94 (SD 10) and 92 (SD 14), respectively (95% CI, 80‐105; p = 0.52) and mean UCLA scores were 6 (SD 1.2) and 6 (SD 1.5), respectively (95% CI, 4‐8; p = 0.49). Five‐ and 10‐year survivorship of the allografts was 93% (95% CI, 77‐98) and 93% (95% CI, 77‐99), respectively. Survivorship at a mean of 5 years in the trabecular metal cones group was 91% (95% CI, 56‐98). With the numbers available, there were no differences between the groups in terms of the frequency of surgical complications (3% [one of 30] versus 7% [one of 15]; odds ratio, 0.5; p = 0.632). Conclusions: With the numbers available, we found no difference in pain, function, or repeat revision when comparing femoral head allografts and trabecular metal cones for severe bone defects during revision TKA. However, we used allografts for the larger bone defects. Based on these results, we believe that femoral head allografts and trabecular metal cones can both be used for the management of Anderson Orthopaedic Research Institute Types 2 and 3 defects. Future multicenter studies are required with larger numbers, cost analyses, and a longer duration of followup. Level of Evidence: Level III, therapeutic study.